Enhanced Phase Synchronization of Blood Flow Oscillations between Heated and Adjacent Non-heated Sacral Skin - Liao, Fuyuan (2012)
The study of skin microcirculation may be used to assess risk for pressure ulcers. It is observed that local heating not only causes an increase in blood flow of the heated skin but also in the adjacent non-heated skin. The underlying physiological mechanism of this indirect vasodilation of the non-heated skin remains unclear. We hypothesized that blood flow oscillations (BFO) in the adjacent non-heated skin area synchronize with BFO in the heated skin, thus inducing a vasodilatory response. We investigated BFO in the heated and adjacent non-heated skin (12.1±1.2 cm distance) on the sacrum in 12 healthy participants. The ensemble empirical mode decomposition (EEMD) was used to decompose blood flow signals into a set of intrinsic mode functions (IMFs), and the IMFs with power spectra over the frequency range of 0.0095–0.02 Hz, 0.02–0.05 Hz, and 0.05–0.15 Hz were chosen as the characteristic components corresponding to metabolic, neurogenic, and myogenic regulations, respectively. Then, the instantaneous phase of the characteristic components was calculated using the Hilbert transform. From the time series of phase difference between a pair of characteristic components, the epochs of phase synchronization were detected. The results showed that myogenic and neurogenic BFO exhibit self-phase synchronization during the slower vasodilation of the heated skin. In the non-heated skin, the degree of synchronization of BFO is associated with the changes in blood flow.